Refillable silicone pump with precise switching for timed therapeutic delivery - Thotathil, Naaz; Amante, John J.; Wingell, Micah; Hutter, Grace W.; Fallon, Ultan; Fan, Yiling; Mendez, Keegan; Roche, Ellen T.; Kearney, Cathal J. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionGiven the precise temporal coordination of natural biological processes, administering therapeutic agents at specific times can be used to enhance efficacy in a range of applications. To achieve such controlled drug delivery, various stimulus-responsive techniques (e.g., ultrasound, temperature changes, and electromagnetic radiation) have been developed. However, many of these current methods exhibit limitations, such as premature leakage prior to stimulus activation or delayed and prolonged responsiveness to stimuli. Our research introduces a soft robotic pressure-actuated drug delivery pump aimed at improving therapeutic efficacy through precisely-timed drug administration.MethodsThis device utilizes silicone – a low-modulus material – for both the therapeutic reservoir and the actuation chamber to create a biocompatible and conformable interface, facilitating controlled drug release and offering the potential to be adapted as an implantable drug delivery system. Two ports in the actuation chamber allow the therapeutic reservoir to be refilled. We actuated the pressure reservoir of the device in the range of 28.5 – 59.8 mmHg and tested: the pressure-dependent release from the device; repeated release; baseline release, and the ability to deliver a wide-range of therapeutics. ResultsImportantly, the system demonstrated a reliable On/Off mechanism – confirmed by actuating to ∼80% of opening pressure over 5 days – which addresses a key limitation in many existing technologies. In vitro, the device was used to deliver a range of therapeutics and had non-significant differences versus manual delivery of therapeutics in relevant assays: antibiotics (doxycycline; reduced E. coli viability by 49.6% vs. 49.8%); adeno-associated virus (AAV; transduced 73.5% vs. 76.2% of cells); dexamethasone (2D fibroblast scratch wound closure 50.9% vs. 51.0%); and successful delivery of viable cells (viability of 83% vs. 100%). We additionally developed a finite element model to model the pressure/volume release trend, and demonstrated the effect of membrane stiffness on release.DiscussionOur results demonstrate that the device can consistently administer therapeutics and molecules of various sizes and functions while maintaining their bioactivity, showcasing its potential for repeated, precisely-timed therapeutic delivery.